Penguatan Kelembagaan PERBAKIN Papua melalui Pelatihan Manajemen Organisasi dan Perencanaan Program Keolahragaan - Soponyono Soponyono; Usman Idris (Edujavare Publishing, 2026)
Strengthening institutional capacity is an essential prerequisite for sports organizations to carry out their coaching, program management, and performance development functions sustainably. This community service activity aims to improve the institutional capacity of PERBAKIN Papua through organizational management training and sports program planning. The method used is participatory training and institutional mentoring involving PERBAKIN Papua administrators. The activity is carried out through the stages of identifying organizational needs, delivering materials, interactive discussions, case studies, practical work program preparation, and evaluating training results. The results of the activity indicate an increase in administrators' understanding of organizational governance, management functions, institutional coordination, organizational administration, and the importance of leadership and communication in managing sports organizations. In addition, participants demonstrated increased ability to develop sports programs that are more systematic, measurable, and in accordance with organizational needs. Administrators are able to formulate program objectives, determine targets, develop implementation schedules, identify resource needs, and establish program evaluation indicators. This activity also strengthened inter-sectoral coordination within the management and resulted in a draft work program that can be used as a guideline for the organization in the following period. Institutional strengthening through training and mentoring has proven to be an effective strategy for enhancing organizational professionalism, improving governance, and supporting more focused and sustainable shooting sports development in Papua.